BUDAYA BIROKRASI DALAM PENINGKATAN PELAYANAN PUBLIK (Studi Kasus Kantor SAMSAT DIY) - , Dyah Wulan Novitasari, S.Hut, Dr. Erwan Agus Purwanto ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In order to service the needs of global markets globalization whichâs developing in Indonesia on the one hand and in the implementation of regional autonomy, which carried by Act No. 32 of 2004 on Local Government on the other hand, bureaucratic administration of districts all over Indonesia are required to change to the culture of bureaucracy in public services effectively and efficiently, as well as Yogyakarta Regional Government. Based on this background, the researcher conducted a study on the Bureaucracy Culture in the Office of the Public Service Improvement DIY with the problem (1) whether the bureaucratic culture that is used in public service, (2) the service unit a bureaucratic culture where it is applied, (3) how the public service after the bureaucratic culture implemented is. To answer these problems, done research using the concept of bureaucratic culture in public services in providing public servants to be more efficient and effective. Bureaucratic culture indicators used include the work culture, discrimination of service, responsibility, communication, behavior of bureaucracy, supervision. In addition, used a qualitative approach with a focus of study or case study. Methods of data collection was done by using observation, interview and distributed questionnaires to the users of the service bureaucracy. The analysis showed that (1) Office Units bureaucratic culture of Yogyakarta is not only rational culture but still running the cultural traditions of the past. For that, there is a mix between the old culture that prioritizes state services and on the other hand there is the emphasis the rational culture of public service with benchmarks that have been set by the government. (2) There are two service units bureaucratic culture of Yogyakarta. First, the service unit representative of the Republic of Indonesia Police carried out by the Police Dirlantas DIY. Second, the Department of Finance and Asset Management Revenue Region Special Province of Yogyakarta). (3) The society evaluation results of the bureaucratic culture of public service after the applicable over all is good.